2009
DOI: 10.1080/00016340902859307
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 and 2 receptors gene polymorphisms in pre‐eclampsia and normal pregnancy in three different populations

Abstract: There is an association between PE/E and the GG-genotype of AT2R in Afro-Caribbean women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
3
31
1
2
Order By: Relevance
“…Studies showed that the distribution of gene polymorphisms differed among different ethnic populations. The result of a meta-analysis is likely to be affected by the population sources of study subjects, and thus the conclusions drawn from studies based on other populations may not be appropriate for a specific population [38]. It is necessary to conduct a meta-analysis to evaluate the associations between ACE I/D, AGT M235T, and PIH among Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the distribution of gene polymorphisms differed among different ethnic populations. The result of a meta-analysis is likely to be affected by the population sources of study subjects, and thus the conclusions drawn from studies based on other populations may not be appropriate for a specific population [38]. It is necessary to conduct a meta-analysis to evaluate the associations between ACE I/D, AGT M235T, and PIH among Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…24 The studies of Seremak-Mrozikiewicz et al in 2005 confirmed the association of the A1166C (AT2R1) polymorphism and pre-eclampsia, but other studies performed by GOPEC (The Genetics of Pre-eclampsia Consortium) researchers, and Akbar et al revealed inconsistent results. [25][26][27] Regarding the polymorphisms located in the renin gene, there are no positive results on the association with the risk of pre-eclampsia. 28 As placental and foetal membranes are important production sites of the RAS components, we also evaluated the possible influence of the mutated newborn RAS genes on the risk of pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 There are controversial reports from different populations related to the role of ACE I/D polymorphism in the pathogenesis of preeclampsia. 1,3,[8][9][10][11][12][13][14][15][16][17] Also, in a few studies the association of AT1R A1166C polymorphism with preeclampsia has been examined. [8][9][10]17 A positive relationship between the degree of oxidative stress and the clinical severity of preeclampsia has been reported, suggesting that the toxic effects of lipoperoxide lead to hypertension, endothelial damage and leukocyte activation.…”
Section: Introductionmentioning
confidence: 99%